2021
DOI: 10.1590/1980-220x-reeusp-2020-0381
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gestational age at term on breastfeeding: a cohort study

Abstract: Objective: To identify the effect of the category gestational age at term on breastfeeding in he first hour of life, the duration of exclusive breastfeeding, and practice of breastfeeding twelve months from birth. Method: Single cohort, with a one-year prospective follow-up of 541 children. A hierarchical analysis was performed, with models adjusted per Cox regression, considering critical p < 0.05. Results: During raw analysis there was a statistical difference on breastfeeding in the first hour of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…This may be due to the small numbers of infants included in the analyses, which may have compromised the statistical power for the comparisons performed. Our study indicated, however, that the use of baby bottles was significantly associated with lower duration of exclusive breastfeeding/prevalence of exclusive breastfeeding duration until the age of three months, corroborating findings registered for non-indigenous children in Brazil 59,60,61 . The negative health and nutritional consequences of baby bottle use are widely known and described in the literature 62 .…”
Section: Discussionsupporting
confidence: 89%
“…This may be due to the small numbers of infants included in the analyses, which may have compromised the statistical power for the comparisons performed. Our study indicated, however, that the use of baby bottles was significantly associated with lower duration of exclusive breastfeeding/prevalence of exclusive breastfeeding duration until the age of three months, corroborating findings registered for non-indigenous children in Brazil 59,60,61 . The negative health and nutritional consequences of baby bottle use are widely known and described in the literature 62 .…”
Section: Discussionsupporting
confidence: 89%
“…Breastfeeding also improves neuropsychological performance, strengthens mother-child bond, reduces the length of hospital stay with lesser incidence of readmissions ( 8 ). In spite of the evidence on benefits of breastfeeding for preterm and small for gestational age (SGA) babies, the knowledge on their breastfeeding practices is scanty in LMICs when compared with term infants ( 9 , 10 ). The data available on preterm births is robust in high income countries with higher birth registration coverage for preterm births in contrast to LMIC’s, where birth registration coverage is low and data on preterm birth is scarce ( 11 ).…”
Section: Introductionmentioning
confidence: 99%